Exploring cyclists’ travel behaviour in different attitudinal market segments: case study of Quelimane, Mozambique - Classio Joao Mendiate; Alphonse Nkurunziza; Julio A. Soria-Lara; Andres Monzon (Urban, Planning and Transport Research, 2023)
ABSTRACTDistinguishing bicycle market segments is relevant to promote bicycle use, as customised policy strategies can be targeted to each submarket. This paper aims to adopt the attitudinal market segmentation approach to identify potential markets of bicycle commuters and their travel behaviour differences. A survey was conducted among 902 commuters in Quelimane, Mozambique. Factor analysis is used to identify key latent factors. Two-step cluster analysis is used to segment the bicycle commuting market into several submarkets. Then, Mann-Whitney U test is used to compare pairs of segments based on a set of travel behaviour factors such as cycling frequency, travel time and commuting mode. Three segments are obtained: Reluctant cyclists (S1), Livelihood cyclists (S2), and Demanding cyclists (S3). The study reveals that S1 cycle less frequently when compared to S2 and S3. S1 can be motivated to cycle more frequently by promoting educational campaigns to increase their perception towards cycling benefits. S1 and S3 commute long hours when compared to S2, thus, promoting distribution of land-use activities to reduce travel distance could motivate bicycle use. S1 frequently walk commute compared to S2 and S3, therefore policies to increase bicycle use were pointed to making bicycles more accessible to Reluctant cyclists.